1989
DOI: 10.1017/s0031182000058637
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of lithium chloride on the insect trypanosomatidHerpetomonas samuelpessoai

Abstract: Effects of lithium chloride on growth, differentiation and respiration of Herpetomonas samuelpessoai, cultivated in a synthetic medium were studied both at 28 and 37 degrees C. Low concentration of lithium chloride (15 mM) stimulated growth at 37 degrees C. In addition, the protozoon tolerated high concentrations (60-150 mM) of the salt at both incubation temperatures. In general, 15 mM lithium chloride increased and 150 mM decreased oxygen uptake when glucose, glutamic acid and proline were used as substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…3), although the percentage of opisthomastigotes remained higher than those obtained in other Herpetomonas species such as H. samuelpessoai , H. muscarum muscarum (Lopes et al 1983) and H. megaseliae (Daggett et al 1972). This surprising observation is not in accordance with foregoing studies of differentiation in members of the Herpetomonas genus, in which opisthomastigotes have been found to appear in culture only at the end of the exponential phase of growth (Esteves et al 1979;Janovy et al 1974;Roitman et al 1976) or after exposure to metabolic inhibitors (Nakamura and Pinto 1989). We have recently demonstrated that elimination of the symbiont of H. roitmani by treatment with the antibiotic chloramphenicol results in an increase in the proportion of opisthomastigotes from 37% to approximately 72% by 72 h after the initial inoculation (Faria-e- Silva et al 1994).…”
Section: Discussionmentioning
confidence: 61%
“…3), although the percentage of opisthomastigotes remained higher than those obtained in other Herpetomonas species such as H. samuelpessoai , H. muscarum muscarum (Lopes et al 1983) and H. megaseliae (Daggett et al 1972). This surprising observation is not in accordance with foregoing studies of differentiation in members of the Herpetomonas genus, in which opisthomastigotes have been found to appear in culture only at the end of the exponential phase of growth (Esteves et al 1979;Janovy et al 1974;Roitman et al 1976) or after exposure to metabolic inhibitors (Nakamura and Pinto 1989). We have recently demonstrated that elimination of the symbiont of H. roitmani by treatment with the antibiotic chloramphenicol results in an increase in the proportion of opisthomastigotes from 37% to approximately 72% by 72 h after the initial inoculation (Faria-e- Silva et al 1994).…”
Section: Discussionmentioning
confidence: 61%
“…Lithium ions at 15 mM when added to culture medium of the protozoan parasite, Herpetomonas, stimulated its growth [30]. Lithium ions at 20 mM concentration inhibited glucose synthesis in the rat liver [31]. Most relevant to the present report that Lithium ions at a concentration of 2-20 mM had a stimulatory effect on insulin induced uptake of α-aminobutryic acid, synthesis of DNA and RNA and cell multiplication of mouse mammary gland explants cultured in a chemically-defined synthetic medium.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation mechanism of H. samuelpessoai is triggered by changes in the culture medium composition, incubation conditions and by adding substances to the culture medium that interact with cellular components. In this context, the cellular differentiation of H. samuelpessoai occurs in the stationary phase and when cell growth is inhibited; also, by high incubation temperature (37°C) or after exposition to metabolic inhibitors like sodium butyrate, 2-deoxy- d -glucose, Concanavalin A, lidocaine, cholinergic drugs and dimethylsulfoxide (DMSO) (Angluster et al 1977; Souza et al 1980; Castellanos et al 1981; Thomas et al 1981 a , b; Nakamura and Pinto, 1989). These substances induce changes in the cell surface saccharide composition (Soares et al 1984; Santos et al 2002 a ), in the cell surface charge (Soares et al 1988), in the protein synthesis (Santos et al 2001), in the phosphatase production (Santos et al 2002 b ) and in the expression of proteolytic enzymes (Santos et al .…”
Section: Introductionmentioning
confidence: 99%